Ukuran Perusahaan, Pertumbuhan Penjualan, Penghindaran Pajak: Bagaimana Peran Tanggung Jawab Sosial Perusahaan? - Stefanie Martchellia Suteja; Amrie Firmansyah; Vania Vashtiany Sofyan; Estralita Trisnawati (Politeknik Keuangan Negara STAN, 2022)
This study examines the effect of firm size and sales growth on tax avoidance by using social responsibility as a moderating variable. The data is in the form of financial information sourced from financial statements and corporate social responsibility information sourced from sustainability reports and annual reports of consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. Based on purposive sampling, the number of samples that can be employed is 75 observations. Hypothesis testing is conducted by multiple regression analysis for panel data. This study concludes that firm size does not affect tax avoidance, while sales growth positively affects tax avoidance. Also, this study found that social responsibility can weaken the positive association between firm size and tax avoidance and sales growth on tax avoidance. This study suggests that the Indonesian Tax Authority should include sustainability issues in preparing tax policies in Indonesia.